Peran Minat pada Pegadaian Digital Service (PDS) Cabang Mojosari: Analisis Persepsi Kepercayaan dan Literasi Keuangan terhadap Keputusan Investasi - Alvionita Zakiyatur; Tri Kartika Pertiwi (Program Studi Manajemen Fakultas Ekonomi UST, 2025)
This study aims to analyze and identify the influence of trust perception and financial literacy variables on investment decisions through interest. The research data consist of primary data obtained from questionnaires and secondary data collected from related institutions and websites. The variables were measured using a Likert scale ranging from 1 to 5. The study population includes customers of Pegadaian Mojosari Branch who save gold through the Pegadaian Digital Service (PDS) application during the 2022–2024 period. The sampling technique applied was purposive sampling with a total of 130 respondents. Data analysis was conducted utilizing a Partial Least Squares (PLS) 3 to examine the relationships between variables. The findings shows that customers consider saving gold through the Pegadaian Digital Service (PDS) application to be highly efficient, which encourages them to maintain their interest in repeatedly using the application for gold investment.